SARS-CoV-2 Infection Increases the Risk of Muscle Injury in Professional Male Soccer Players-A Retrospective Analysis of the Italian and Spanish Major Leagues - Sandra Miccinilli; Marco Bravi; Giorgio Conti; Federica Bressi; Silvia Sterzi; Fabio Santacaterina; Massimo Ciccozzi (MDPI AG, 2023)
A retrospective cohort study on professional soccer players from the Serie A and LaLiga was conducted to investigate the correlation between SARS-CoV-2 infection and muscle injuries. Players were divided into two groups based on whether they contracted the SARS-CoV-2 infection (C+) or not (C−) during the 2020/2021 season. In the 2019-2020 season, both championships showed a similar number of muscular injuries (MI) between C+ and C− (Serie A: p = 0.194; 95% CI: −0.044 to 0.215, LaLiga p = 0.915; 95% CI: −0.123 to 0.137). In the 2020-2021 season, C+ had a significantly higher number of MI compared to C− in both championships (Serie A: p < 0.05; 95% CI 0.731 to 1.038; LaLiga: p < 0.05; 95% CI: 0.773 to 1.054). Multiple linear regression analysis confirmed that belonging to C+ in the season 2020/2021 was the variable that most strongly influenced the probability of having a muscle injury. Survival analysis revealed a hazard ratio of 3.73 (95% CI 3.018 to 4.628) and of 5.14 (95% CI 3.200 to 8.254) for Serie A and LaLiga respectively. We found an association between SARS-CoV-2 infection and increased risk of muscle injury, emphasizing the importance of carefully considering the infection in the decision-making process for returning to sport. Therefore, SARS-CoV-2 infection should be judged as a real injury requiring specific assessment and training programs.